Politique de revitalisation et nuits urbaines : le cas de Bordeaux - Cécilia Comelli (L'Espace Politique)
This paper focuses on the links between urban policies and the night in Bordeaux. It shows the policy of revitalization of the city-center conducted since 1995 when Alain Juppé was elected as Mayor, and its consequences on spaces and times for the different users. This policy is responsible of a deep change on the areas targeted, morphologically and sociologically, and produces specific temporalities. The approach taken postulated that socio-spatio-temporal changes cause a conflicting sharing of spaces and times, especially between inhabitants, night people and entertainment institutions, which offer has strongly increased since the last few years. Therefore, this paper focuses on the impact of urban projects on the festive dimension of the urban night. These new practices do not seem to be taken as an economic opportunity by the local authorities who try to limit them.